(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Endocrine ophthalmopathology (EOP) is a progressing chronic disease of the soft tissues of the orbit and eye, developing against the background of the thyroid dysfunction with the unfavorable visual and cosmetic outcome, affecting work able at the age of35—59. Purpose. To investigate a condition of the retina of the macular area in patients with EOP according to the data of optical coherent tomography. Material and methods. Optical coherent tomography (OCT) was made in 103 eyes of 55 patients with EOP by the device « Stratus OCT model 3000 of the firm «Karl Zeis». The results obtained were compared to the data of examination of 69 eyes without ophthalmopathology. The analysis of the data is made with the use of the program Statistics 9.0. Results and their discussion. It was established by OCT that average thickness of the retina in the fovea of the patients with EOP has made (212.8+32.9) pm that was by 18.3pm higher than in the norm (194.5+22.22) pm. The average thickness of the retina around the fovea varied depending on the direction of measurement and was higher than in the norm in all zones and sectors of measurement. Thickness of the macular area of the retina both in the internal and external zones of the investigation in all sectors was authentically higher than in the central one (p <0.0000), it was higher in the internal zone than in the external one. In comparison of the data of thickness of the retina in the upper and lower as well as nasal and temporal sectors it is established that thickness of the retina from the nasal side is authentically higher than with from the temporal one both in the three-millimetric (p <0.01) and in six-millimetric (p <0.0000) zones and it is practically identical in the upper and lower sectors (0.05). By means of OCT it was possible to reveal preclinical manifestation of retinal edema in the macular area in 45.5 % of cases, to administer adequate treatment and receive good result. Conclusions. OCT should be included in the protocol of examination of patients, with EOP as an obligatory method of the investigation as it allows to reveal the initial stage of edema even in absence of clinical manifestations.